2020
DOI: 10.1159/000508337
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complexity of Lymphovascular Invasion: The Role of Cell Migration in Breast Cancer as a Prototype

Abstract: Lymphovascular invasion (LVI) is associated with poor outcome in breast cancer (BC); however, its underlying mechanisms remain ill-defined. LVI in BC develops through complex molecular pathways involving not only the interplay with the surrounding microenvironment along with endothelial cells lining the lymphovascular spaces but also changes in the malignant epithelial cells with the acquisition of more invasive and migration abilities. In this review, we focus on the key features that enable tumour cell detac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 117 publications
2
28
0
Order By: Relevance
“…The cell migration capacity is essential for disease progression and is considered the first step for lymphovascular invasion and tumor metastasis [ 24 ]. The data obtained by the wound-healing assay showed that D3 cells had a significant delay in wound closure capacity, nearly 30%, in all analyzed time points when compared to EV cells ( Figure 3 ; p = 0.027 at 3 h and p < 0.0001 at 6 h, 9 h, 12 h, and 15 h).…”
Section: Resultsmentioning
confidence: 99%
“…The cell migration capacity is essential for disease progression and is considered the first step for lymphovascular invasion and tumor metastasis [ 24 ]. The data obtained by the wound-healing assay showed that D3 cells had a significant delay in wound closure capacity, nearly 30%, in all analyzed time points when compared to EV cells ( Figure 3 ; p = 0.027 at 3 h and p < 0.0001 at 6 h, 9 h, 12 h, and 15 h).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms underlying LVI are unclear. In their review, Kariri et al [ 26 ] state that “understanding the role of cancer cell invasion and migration in the differentiation of LVI-related molecular alterations from these driving tumor cell invasion and migration as an early mechanism associated with malignancy is a ‘difficult’ but ‘beatable’ challenge.” However, several hypothetical mechanisms have been proposed. Ribelles et al [ 27 ] suggested that genetic alterations can increase migratory potential.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of LVI represents a manifestation of an interaction between the tumor and its microenvironment. The molecular mechanisms underlying LVI are complex and not fully defined, but pathways involving cytokine-receptor interactions have been implicated [26][27][28] . Studies evaluating racial differences in BCA tumor microenvironment have described the differential expression of genes associated with inflammation and angiogenesis 24,25,[29][30][31] , as well as increased microvessel density 29,31 and increased numbers of tumor-associated macrophages 29,32 , which correlate with increased lymphangiogenesis and LVI [33][34][35] , in tumors belonging to Black women.…”
Section: Introductionmentioning
confidence: 99%